The Influence of the Number Head Together (NHT) Cooperative Learning Model on Improving Results Student's Mathematics Learning - Putri Sonia Br Simarmata; Elma Batasia Siregar (International Journal of Educational and Psychological Sciences, 2023)
With use model learning cooperative type Numbered Head Together (NHT) in process learning, able to create materials Which served more easy under stood learners, learner scap able explorehis knowledge Alone, And learner scap able finish problem Which set which states that the N umbered Head T ogether (NHT) type cooperative learning model can improve learning outcomes. The aim of this research is to determine the effect of the Numbered Head Together (NHT) cooperative learning model on improving students' mathematics learning outcomes. The research method used is Systematic Literature Reviewby collecting data from scientific journals, books and other related sources. Based on the results of research using the Systematic Literature Review method, it can be concluded that the application of the Numbered Head Together (NHT) learning model has an effect on students' mathematics learning outcomes, namely that it can improve students' mathematics learning outcomes. Literature data sources obtained and analyzed stated that the mathematics learning outcomes of students who used the Numbered Head Together (NHT) learning model were higher than those using the conventional model.